Arquitetura cliente-servidor em jogos multiplayer - Picoli, Ivan Luiz (2011)
Game developing involves several areas of knowledge. A multiplayer game allows users to interact in the same environment, seeing the actions executed on remote computers controlled by other players, who can be located in different and distant places. A multiplayer game is a distributed system and for their processes to communicate, it is required the dispatch of messages through the network. Developing a pattern of messages that allows a higher performance of the game is a task that requires a previous analysis. This work proposes a network architecture and a message pattern that decrease the network traffic in multiplayer games, and allow the remote objects of the players to show up synchronized on all clients connected to the same distributed environment, with their corrected coordinates and movements performed in real time.